The empowered patient how to get the right diagnosis, buy the cheapest drugs, beat your insurance company, and get the best medical care every time - Cohen, Elizabeth 1935- (New York Ballantine Books Trade Paperbacks, 2010)
"Combining the personal stories of patients across America with crucial advice on receiving the best possible health care, this guide will enable you to confront and often confusing and perilous system--and come out ahead" --Cover, p. 4.
How to be a "bad patient" -- How to find Dr. Right (and fire Dr. Wrong) -- Don't leave a doctor's appointment saying "Huh?" -- How to avoid a misdiagnosis -- How to become an Internet MD (medical detective) -- You vs. the insurance industry -- How to get good drugs cheap -- Don't fall for medical marketing -- Don't let a hospital kill you.
Includes bibliographical references (p. [193]-208) and index.
Keywords: Patient education; Health counseling; Patient Education As Topic; Patient Participation